Efektivitas Pendekatan Pendidikan Matematika Realistik Indonesia Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematika - Mayesty, Desintha Paxia; Khuzaini, Nanang; Sustianta (EduCurio: Education Curiosity, 2024)
This research aims to determine the effectiveness of the Indonesian Realistic Mathematics Education approach in enhancing students' understanding of mathematical concepts. The study employs a quasi-experimental design. The population for this research includes all twelfth-grade students at SMAN 1 Sedayu. The instrument used in this study is a test measuring mathematical concept understanding. Non-parametric tests were conducted to test the research hypothesis include the Wilcoxon signed-rank test and the Mann Whitney U test. The Wilcoxon Signed Rank Test indicates significance (0.000 < 0.05), that means is rejected. However, the Mann-Whitney U test yields an Asymp. Sig. (2-tailed) value of 0.617, leading to the acceptance of Therefore, it can be concluded that the Indonesian Realistic Mathematics Education approach is not effective in improving the mathematical concept understanding of students of XII MIPA 3.